Structural characterization of mammalian bHLH-PAS transcription factors - Wu, D; Rastinejad, F (Elsevier, 2016)
The mammalian basic helix-loop-helix-PER-ARNT-SIM (bHLH–PAS) transcription factors share common architectural features that include a bHLH DNA-binding domain and tandemly positioned PAS domains. The sixteen members of this family include the hypoxia-inducible factors (HIF-1α and HIF-2α), ARNT (also known as HIF-1β), CLOCK and BMAL1. Most bHLH-PAS proteins have been genetically linked to variety of diseases in humans, including cancers, metabolic syndromes and psychiatric conditions. To function as transcription factors, the bHLH-PAS proteins must form heterodimeric complexes. Recent crystallographic studies of HIF-α-ARNT and CLOCK-BMAL1 complexes have unveiled the organization of their multi-domain bHLH-PAS-A-PAS-B segments, revealing how these architectures can give rise to unique patterns of heterodimerization. As our structural understanding becomes better integrated with ligand-discovery and target gene identification, a more comprehensive picture of their architectural and functional properties will emerge.